Strategic Pathways for Young Universities to Accelerate The Ranking Success - Mamajonova Mukhlisakhon Muzaffar kizi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: University rankings have become influential benchmarks for assessing institutional quality and competitiveness in global higher education. Specific Background: Young universities in developing countries face unique challenges in gaining international recognition due to limited historical prestige and resource constraints. Knowledge Gap: Existing literature rarely addresses how such institutions can strategically align their internal strengths with ranking methodologies to accelerate global visibility. Aims: This study explores how New Uzbekistan University (NUU) can leverage the Times Higher Education (THE) World University Rankings methodology to achieve rapid advancement. Results: Through comparative analysis of THE and QS rankings, case studies of high-performing young universities (e.g., Paris-Saclay, PSL Paris, NTU Singapore), and strategic mapping, the research reveals that NUU’s partnerships with MIT and TUM, along with government support via Presidential Decree PQ-151, align with THE’s research-focused criteria (59% weighting). Novelty: The study introduces a three-phase roadmap enabling young universities to achieve THE Young University Rankings entry within five years and main rankings placement within ten years—5–7 years faster than traditional models. Implications: This framework offers the first evidence-based strategy for young institutions to convert structural advantages into measurable ranking outcomes while ensuring educational quality and long-term sustainability. Highlights: Highlights how NUU leverages MIT and TUM partnerships for rapid advancement. Emphasizes THE’s research-focused methodology as optimal for young institutions. Introduces a 3-phase roadmap for achieving global ranking within a decade. Keywords: The Rankings, Young Universities, Strategic Partnerships, Research Metrics, Higher Education Strategy